Numerical analysis of slow and fast light effect in semiconductor optical amplifier with certain facet reflection - Qin, Cui; Jiang, Yu; Zhen, Li (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
In this paper, the slow and fast light (SFL) effects of the semiconductor optical amplifier (SOA) having certain facet reflections are theoretically investigated. The theoretical model is used to account for the SFL phenomenon causing the coherent population oscillation. The influence of the current modulation frequency, the value of the current, the linewidth enhancement factor, facet reflectivity as well as the relative phase of the modulated current on the phase delay in the SOA are studied. It is demonstrated that the SFL effect could be controlled by the modulation frequency, the value and relative phase of the current. Finally, it is shown that the magnitude of the SFL delay could be tuned by a change in the linewidth enhancement factor as well as the facet reflectivity of the SOA.
Optica Applicata, Vol. 52, 2022, nr 4, s. 655-667
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; semiconductor optical amplifiers; slow and fast light; coherent population oscillation